2018
DOI: 10.4045/tidsskr.17.0338
|View full text |Cite
|
Sign up to set email alerts
|

Bruk av tvang i psykisk helsevern – dilemmaer i beslutningsprosessen

Abstract: Latitude should be given for ethical and professional reflection in relation to assessing the use of coercion in daily clinical practice, as well as training in measures to reinforce patients' experience of participation during the interview.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…The experience of users can also be improved by placing attention on therapeutic relationships and on the attitudes and behaviour of professionals, in addition to reducing coercive measures. According to Berge et al (2018), professionals should express their concern and empathy towards users and strive to improve their own communication abilities before, during and after a coercive incident. When treated with respect and involved in the decision-making process, users report a less negative perception of coercion and greater satisfaction with mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of users can also be improved by placing attention on therapeutic relationships and on the attitudes and behaviour of professionals, in addition to reducing coercive measures. According to Berge et al (2018), professionals should express their concern and empathy towards users and strive to improve their own communication abilities before, during and after a coercive incident. When treated with respect and involved in the decision-making process, users report a less negative perception of coercion and greater satisfaction with mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Decision-making processes leading to involuntary admission often imply uncertainty and doubt among the clinicians in charge (16). In a qualitative interview involving psychiatrists, Feiring and Ugstad showed that legal criteria regulating the use of compulsory admissions are often being interpreted by clinicians and that decisions are influenced by extra-legal factors, such as patients’ needs and attitudes toward treatment, follow-up options, and social circumstances (17).…”
Section: Discussionmentioning
confidence: 99%
“…Dessuten ble det foretatt bruker-spør-brukerintervjuer av pasienter som var involvert i de samme samtalene. Resultatene fra intervjuene med de øyeblikkelig hjelp-ansvarlige er publisert (9).…”
Section: Man Må Forsøke å Påføre Pasienten Minst Mulig Tap Av Verdighetunclassified